Laju Pembakaran Briket Limbah Cangkang Kulit Kopi, Sekam Padi Dan Tempurung Kelapa Sebagai Energi Alternatif Ramah Lingkungan - Mafisca, Deara; Wahyuni, Ike Dian; Yuniastuti, Tiwi (Poltekkes Kemenkes Bengkulu, 2025)
Briquettes are an energy source derived from biomass which can be used as an alternative energy to replace petroleum and other fossil-based energy. Utilizing biomass waste as an alternative energy source can reduce waste and pollution while also providing renewable energy. The purpose of this research is to analyze the combustion rate of briquettes made of coffee husks, rice husks, and coconut shells. This research used a Pre-Experimental design with a comparative descriptive approach, and analyzed by using the Kruskal-Wallis test. In this design, the treatment or intervention is applied to the samples (X), and then a measurement or observation of the post-test results (O2) is conducted. Since there is no control group, the measurement results (O2) are descriptive and used to compare outcomes between treatments. The results indicate that the type of raw material significantly affects the combustion rate (χ² = 7.600, p = 0.020). Coffee shell briquettes have the highest combustion rate (1.38 g/min), burning quickly, efficiently, and steadily. Rice husk briquettes show a moderate rate (0.59 g/min) with higher ash residue, while coconut shell briquettes burn the slowest (0.53 g/min) but have the longest duration and a stable flame. These differences are related to the physical and chemical characteristics of the raw materials, including density, fixed carbon content, moisture level, and silica. The findings confirm that agricultural waste has potential as an alternative energy source, which can be tailored according to needs: coffee shells for rapid heat, coconut shells for long duration, and rice husks for abundant raw material availability.